To evaluate the relative influence of coefficient of friction on the motion of golf ball (speed and roll) during golf putt - Griffiths, I.; McKenzie, R.; Stredwick, H.; Hurrion, P. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
Pace control and green reading have been highlighted as important aspects of a golfer`s arsenal when it comes to putting. The purpose of this study was to compare the ball roll characteristics across eight different surfaces and more specifically analyse the distance it takes for a golf ball to achieve pure rolling motion. Two different methods of collecting putting data were used during this study; a putting robot and a human subject. For each surface thirty putts were tracked for the first 40cm of their travel, namely; a putting mat, rubber, MFC, compact carpet, brass, PTFE, MDF and nitrile rubber, via a high speed camera (360 frames per second). A numerical model was used to determine the mean coefficient of kinetic friction from each of the eight surfaces. Results showed that the surface with the highest coefficient of friction (µ = 0.40), allowed the ball to enter true roll at the earliest stage (3.94"), whereas the surface with the lowest coefficient of friction (µ = 0.11 ), allowed the ball to enter pure roll at the latest stage (16.77"). Knowledge of this negative relationship may have great significance for golf coaches, players who are looking to improve their green reading skills, and golf course designers/greens keepers who are trying to further understand and improve putting greens.